2001
DOI: 10.1007/bf02704741
|View full text |Cite
|
Sign up to set email alerts
|

Current status of fertility control methods in India

Abstract: Approximately 48.2% of couples of 15 to 49 years of age practice family planning methods in India. Female sterilization accounts for 34.2%, with male sterilization declining from 3.4% in 1992-93 to 1.9% in 1998-99. Use of the condom increased to 3.1% from 2.4%. There is an urgent need for research to develop new contraceptive modalities especially for men and also for women and to make existing methods more safe, affordable and acceptable. Current efforts in India to develop a male contraceptive are mainly dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 99 publications
0
15
0
Order By: Relevance
“…4 of age were reported practicing family planning methods in India. 5 Contraceptive "ever users" rate was found to be 75% in Delhi. 6 Whereas, almost half of the subjects were using some family planning methods in Orissa and about 1/3 rd of them relied on traditional method of contraception.…”
Section: Discussionmentioning
confidence: 98%
“…4 of age were reported practicing family planning methods in India. 5 Contraceptive "ever users" rate was found to be 75% in Delhi. 6 Whereas, almost half of the subjects were using some family planning methods in Orissa and about 1/3 rd of them relied on traditional method of contraception.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, it is reported to possess a wide range of pharmacological properties such as antitumor, anti-inflammatory, analgesic (Chitra et al, 1994), antihyperlipidemic, antihyperglycemic (Mahendran et al, 2011a), antifertility (Sharma et al, 2001), anticonvulsant (Mahendran et al, 2011b), cardioprotective (Bhandari et al, 2008), antioxidant (Joshi et al, 2007) and wound healing properties (Kumara Swamy et al, 2007). Embelin showed protective effect against ulcerative colitis induced by acetic acid in rats (Thippeswamy et al, 2011) and dextran sodium sulfate in mice (Kumar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…9 Sharma et al found that 48.2% of couples use family planning methods in India. 10 Contraceptive "ever users" rate in Delhi was found to 75% in study conducted by Bhasin et al 11 The study done in Orissa by Kirkkola et al showed that almost half of the subjects were using some family planning methods. 12 Men being the dominant decision makers regarding family affairs in developing countries can directly or indirectly affect women"s reproductive health.…”
Section: Discussionmentioning
confidence: 98%